Alternative discourse for constituting subjecthood of women: A case for an autonomous feminist discourse in Kashmir in India - Sharma, Divyangna (Frontiers in Political Science, 2023)
The article is centrally concerned with mapping out the autonomy of the feminist subject in India using the case study of Kashmir after the abrogation of Article 35A. It argues that the autonomy of the feminist subject in India has been subsumed within various other discourses due to which the feminist subject of the discourse is still denied the necessary space. The article uses the case study of Jammu and Kashmir and argues that women face triple jeopardy being subjected to multiple counter-discourses to their autonomy. Feminism and autonomy in Kashmir cannot be defined in isolation; gender power relations intersect with the ethnic conflict of Partitions as well as the militarisation of Kashmir. It accounts for women's positions throughout history, including the ancient monarchical system, which resulted in a syncretic Kasmiriyat tradition, the Dogra regime with its alliances and misalignments with British rule, and the violence of the Indian subcontinent's partition. Based on multiple variables, the article employs a two-pronged approach. The first approach is to carry out the discursive analysis of autonomy of the feminist subject in India and Jammu and Kashmir, second approach considers the narrative of Kashmiri women through detailed interviews to determine how they define their autonomy themselves. Using these two approaches an attempt is made to investigate the implications of abrogation of Article 35A in terms of conceptualising a case of autonomous space for Kashmiri women as democratic citizens of India.